Evaluasi Pelayanan SIPRAJA dalam Pengurusan Data Penduduk di Kecamatan Taman Sidoarjo - Dianingtyas, Ayu; Roekminiati, Sri (Universitas Dr. Soetomo Surabaya, 2024)
Efficient and responsive public services play a crucial role in meeting the diverse needs of the community. Sidoarjo Regency has successfully addressed challenges in public services by developing an information technology-based application called SIPRAJA. This application aims to improve the quality and accessibility of public services, particularly in managing population data in Taman District, Sidoarjo. Before the introduction of SIPRAJA, the community faced difficulties accessing information and public services due to limited communication and technology infrastructure. SIPRAJA has successfully increased community access through a digital platform. This qualitative research focuses on accessibility, community satisfaction, and fairness, revealing the need for improvements in SIPRAJA services in Taman District, such as optimizing accessibility to overcome challenges in service locations. The government has also enhanced its responsiveness to community complaints and addressed issues of inequality in managing population data. Recommendations include enhancing digital literacy through training programs and maintaining internet quality. This research provides insights for local governments to understand community expectations for digital public services, aiming to improve service quality and community satisfaction. It emphasizes the importance of ongoing evaluation for the effectiveness and efficiency of public service applications.